TINDAK TUTUR REPRESENTATIF DALAM ANTOLOGI NASKAH DRAMA SARAPAN TERAKHIR - wijayanti, Marita wijayanti; Tajuddin, Shafruddin; Anwar, Miftahulkhairah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2021)
This research aims to describe representative speech act in the antology of drama script “Sarapan Terakhir”. This research is a qualitative descriptive study. The object of this research is representative speech act in the antology of drama script “Sarapan Terakhir”. The data source of this research is the speeches of the characters in the antology of drama script “Sarapan Terakhir”. Data collection techniques used in this study are library techniques, namely reading, listening, recording, and analyzing. Based on the results of the study, there were a number of representative speech acts from three drama texts in the antology of drama script “Sarapan Terakhir” Based on the results of the study, showed that the representative speech act stating there are 78 data, most widely used in the antology of drama script “Sarapan Terakhir”. Second, followed by a representative speech act sugesting there are 75 data. Third, representative speech acts reported 51 data. Fourth, representative speech acts complaining that there are 50 data, Fifth, representative speech acts claim 46 data. Sixth, representative speech acts boasting there are 9 data.